Effect of new and old pesticides on Orius armatus (Gross)—an Australian predator of western flower thrips, Frankliniella occidentalis (Pergande). Issue 3 (7th August 2013) - Broughton, Sonya; Harrison, Jessica; Rahman, Touhidur
Abstract BACKGROUND Orius armatus (Gross) is an important predator of western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) in Australian glasshouse grown sweet pepper. The failure of O. armatus to establish in some glasshouses has been attributed to the use of newer, more non‐selective pesticides, some of which are regarded to be compatible with integrated pest management. The residual toxicity (via direct and indirect contact) of several older and newer chemistry pesticides were evaluated. In addition, the effect of several systemic insecticides through insecticide‐treated food‐chain uptake was tested. RESULTS Older chemistry pesticides (methamidophos, dimethoate) were toxic to Orius armatus, except pirimicarb which was non‐toxic. Newer chemistry pesticides differed in their suitability. Abamectin was toxic to adults and nymphs. Chlorantraniliprole, imidacloprid and spirotetramat were non‐toxic. Spinosad and spinetoram were moderately toxic to O. armatus. Spinosad also reduced fecundity by 20% compared to the untreated control. Pymetrozine was non‐toxic, but females exposed to treated beans produced 30% fewer eggs and 20% fewer nymphs hatched compared to the untreated control. CONCLUSIONS The selective pesticides do not necessarily facilitate the conservation of beneficials, and further assessment of the various developmental stages and other sub‐lethal effects of chlorantraniliprole, imidacloprid, pymetrozine, spinetoram, and spirotetramat is recommended. © 2013 Society of Chemical Industry